(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
As education increasingly embraces digital transformation, the preparedness of pre-service teachers to integrate technology into their future classrooms becomes a key focus of teacher education programs (Ertmer & Ottenbreit-Leftwich, 2010). This study “Exploring the Correlation Between Digital Literacy and Technology Integration Readiness in Pre-Service Teacher Education” investigates the correlation between digital literacy levels and technology integration readiness among pre-service teachers. Utilizing a quantitative research design, data were collected through standardized digital literacy assessments and technology integration self-efficacy surveys administered to teacher trainees across multiple institutions (Lei, 2009). The results indicate a significant positive correlation, suggesting that higher digital literacy strongly aligns with increased confidence and preparedness to use technology in pedagogical contexts (Tondeur et al., 2020). The study also identifies specific areas where digital literacy training enhances practical tech-integration skills (Spiteri & Rundgren, 2020). Findings advocate for the inclusion of robust digital competence modules in teacher education curricula to ensure that future educators are not only tech-savvy but also pedagogically prepared to leverage technology for effective teaching and learning (Voogt et al., 2015).